Modulation of TRAF6 function by the vaccinia virus protein A52 - Hurst, Tara (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2008)
Large DNA viruses, like Vaccinia virus (VACV), encode numerous proteins that are not essential for viral replication but which modulate the antiviral immune response. A number of VACV immunomodulatory proteins have been found to target different components of the innate immune response, including interleukin-1 receptor/ Toll-like receptor (IL-1R/TLR) signalling pathways. The VACV protein A52 has previously been shown to interact with two members of the IL-1R/TLR signalling pathways, TRAF6 and IRAK2. Further, A52 is a potent inhibitor of IL-IR/TLR-induced NF-kB activation, likely by inhibiting the function of IRAK2. Interestingly, A52 was also found to activate p38 MAP kinase (MARK), enhancing TLR-dependent IL-10 induction. The interaction between A52 and TRAF6 was found to be crucial for A52-induced MARK activation.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin